Dentists' restorative decision‐making and implications for an 'amalgamless' profession. Part 5: knowledge factors. (24th July 2017) - Alexander, G; Hopcraft, MS; Tyas, MJ; Wong, RHK
Abstract: Background: A phase‐down of amalgam in Australia is possible given the Australian Government intends to ratify the Minamata Convention. There is little research as to the influence of a dentist's knowledge on decision‐making, which may be of use when determining the impact of any change. Methods: An online survey relating to aspects of and attitudes to use of direct restorative materials was distributed to all dentists who were members of the Australian Dental Association or Members or Fellows of the Royal Australasian College of Dental Surgeons. Results: There were 408 respondents. Fifty‐eight per cent agreed that there was consistency in undergraduate teaching. Fifty‐two per cent stated that there was a difference between undergraduate teaching and the 'real world'. Postgraduate education was ranked the most important influence on decision‐making. Ninety‐six per cent stated that knowledge of the evidence base is important and 89% believed that they practised evidence‐based dentistry. Conclusions: Dental schools need to maintain teachers' and students' understanding of the evolving technology of direct restorative materials. There is a perceived disconnect between undergraduate teaching and the 'real' world. The evidence base is viewed as confusing, contradictory and not readily understandable. The creation of clinical guidelines would be useful.